EdBox: uso da tecnologia IoT para o controle inteligente de medicamentos - Aguiar, Thaise Pessoa de (Brasil, 2024)
The 21st century world demands connection and rationalization in human activities so that technology has become a necessary means to meet these new parameters. With this reality in mind, this work seeks to bring Internet of Things (IoT) technology, applying its concepts in a prototype of an automated system for medication management. This proposal aims to resolve the difficulty of medication management for users and increase their adherence to prescribed treatment. To this end, the experimental method was used in three stages: bibliographical review for the theoretical foundation, construction of the prototype, called EdBox and functional testing. As a result, the prototype was executed and worked as expected.